SPIRITUAL CARE AND KIDNEY DISEASE IN NZ: A QUALITATIVE STUDY WITH NEW ZEALAND RENAL SPECIALISTS. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - MacLeod, Roderick; Egan, Richard; Walker, Rob; Wood, Sarah; Mountier, Jane
Abstract : Background: People with chronic kidney disease have a shortened life expectancy and carry a high symptom burden. Research suggests that attending to renal patients' spiritual needs may contribute to an improvement in their quality of life and this combined with the burden of renal disease underscores the need to better understand all domains of patients' well-being, including spirituality. The aim of this qualitative study was to investigate the provision of spiritual care in New Zealand renal units from the perspective of specialists. Methods: The study was qualitative using semi-structured interviews and thematic analysis. Participants were recruited across New Zealand's ten renal centres. Participants were asked about their understandings of spirituality, patients' spiritual needs, current service provision of spiritual care, pre- and in-service spiritual care training, and suggestions for improvements. Results: Five specialist doctors and nine specialist nurses were recruited for interviews in 2012. Understandings of spirituality were broad, with most participants having an inclusive understanding. Patients' spiritual needs were generally acknowledged and respected, although not specifically named. Formal spiritual assessments were not done. Consideration of death was discussed as an often-unexamined need. The dominant position was that the specialists did not provide explicit spiritual care of patients but there was some ad hoc provision offered through pre-dialysis educators, family meetings, and Maori liaison staff members. Participants had received no pre-service education or training and very little in-service training in spiritual care. The nurses thought further training "would be useful" but the doctors were less interested. There were many suggestions for improvements. Conclusion: Most participants indicated they would attempt to provide some form of spiritual care, but they generally demonstrated a lack of confidence and awareness of how to address a patient's spiritual and end of life needs.